Methodological Strategies that Influence in Development of the English Language Learning during the Second Semester, 2020 - Jimenez, Alvaro José | Picado, Henry Wilner | Fonseca, Tatiana Bersay | Alvarado, MSc. Mauricio Alvarado MSc. Mauricio (Nicaragua | MATAGALPA UNAN FAREM Matagalpa, 2021)
The use of non-verbal skills has a great impact on the development of listening skills, considering this way how children learn their native language. This research determines the role of Non -verbal skills have in the development of listening skills. As well as that, the following instruments were administered: an observation guide, an interview to the teacher (see appendix 1), and a survey applied to EFL learners randomly selected (see appendix 2). The observation guide was conducted with the aim to verify the presence of non-verbal skills at the moment of teaching and learning. The interview allowed to do a diagnostic about the knowledge that the teacher has about the use of non-verbal skills. The survey was administered to EFL learners to make sure if the strategy previous applied was effective. Results showed, EFL learners can acquire, in a better way, listening skills through non-verbal skills. The most teachers use only traditional non-verbal skills; for this reason, it is advisable to use different non-verbal skills to improve listening skills
Seminario-(Licenciados en Ciencias de la Educación con mención en Inglés)-Universidad Nacional Autónoma de Nicaragua
Seminario (Licenciatura en Ciencias de la Educación, con mención en English) Universidad Nacional Autónoma de Nicaragua
Keywords: Estrategias metodológicas&#x0D